2014
DOI: 10.1590/0104-1843000000004
|View full text |Cite
|
Sign up to set email alerts
|

Resultados das Intervenções Coronárias Percutâneas Primárias Realizadas nos Horários Diurno e Noturno

Abstract: RESUMOIntrodução: Estudos demonstram que a intervenção coronária percutânea primária realizada fora do horário de rotina está relacionada a pior prognóstico. Nosso objetivo foi avaliar os desfechos da intervenção coronária percutânea primária realizada nos períodos diurno e noturno em um centro cardiológico de referência. Métodos: Estudo de coorte prospectivo, que incluiu 1.108 pacientes consecutivamente atendidos por infarto agudo do miocárdio com supradesnivelamento do segmento ST, divididos nos grupos inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…These characteristics are in line with the European and national studies that had larger samples. [15][16][17][18] The median door-to-balloon time observed in this study was within the 90 minutes recommended by international guidelines, 5 with the exception of the procedures performed on weekends. Significant differences were observed in door-to-balloon time in primary PCI conducted during working days when compared to weekends, although there was no difference in door-to-balloon time when comparing day and night shifts or on-hours and off-hours.…”
Section: Discussionsupporting
confidence: 61%
“…These characteristics are in line with the European and national studies that had larger samples. [15][16][17][18] The median door-to-balloon time observed in this study was within the 90 minutes recommended by international guidelines, 5 with the exception of the procedures performed on weekends. Significant differences were observed in door-to-balloon time in primary PCI conducted during working days when compared to weekends, although there was no difference in door-to-balloon time when comparing day and night shifts or on-hours and off-hours.…”
Section: Discussionsupporting
confidence: 61%
“…According to research done in Rio Grande do Sul State, the femoral route was more prevalent. However, a survey conducted in Bosnia and Herzegovina and another one conducted in the city of Marília -SP, the radial route predominated, respectively 70.8% and 94.3% (23)(24) . Analysis performed in the United States has shown that the radial approach is safer than the femoral approach, since they are less likely to cause complications, such as hemorrhage, hematoma formation, thrombophlebitis, ecchymosis and pseudoaneurysm (30) .…”
Section: Discussionmentioning
confidence: 95%
“…In relation to the treated coronary, the Mid Left Anterior Descending Artery (elective and urgency), followed by the Right Coronary Artery, predominated. Studies have confirmed that the most commonly treated coronary artery in patients performing PCI is the Mid Left Anterior Descending Artery and secondly the Right Coronary Artery (21)(22)(23)(24) .…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations